Physicochemical study of the formation of complexes between pancreatic proteases and polyanions - Lombardi, Julia (2015)
The formation of insoluble complexes between proteins and oppositely charged polyelectrolytes was assessed. Two pancreatic enzymes: trypsin and chymotrypsin, and two anionic synthetic polyelectrolytes: polyacrylate and polyvinylsulfonate, were used for the study at the pH range between 3.00 and 5.00. Two different titration curve shapes, representing two insoluble complexes formation mechanisms, were found. The turbidity of enzyme–polyelectrolyte mixtures is related to the increase either in the size or in the quantity of the insoluble complexes. Ionic strength destabilized insoluble complex formation. Finally, the kinetics of the process of insoluble complex formation at different conditions was studied.